Xiphoid Surface Temperature Predicts Mortality in a Murine Model of Septic Shock. Issue 2 (August 2018) - Laitano, Orlando; Van Steenbergen, David; Mattingly, Alex J.; Garcia, Christian K.; Robinson, Gerard P.; Murray, Kevin O.; Clanton, Thomas L.; Nunamaker, Elizabeth A.
Abstract : ABSTRACT: Sepsis continues to be a major challenge for modern medicine. Several preclinical models were developed to study sepsis and each has strengths and weaknesses. The cecal slurry (CS) method is a practical alternative because it does not require surgery, and the infection can be dosed. However, one disadvantage is that the dosage must be determined for each CS preparation using survival studies. Our aim was to refine a survival protocol for the CS model by determining a premonitory humane endpoint that would reduce animal suffering. Mice become hypothermic in sepsis; therefore, we tested whether reductions in surface temperature (Ts ), measured by noninvasive infrared thermometry, could predict eventual death. We injected 154 C57BL/6J mice with CS (0.9–1.8 mg/g) and periodically monitored Ts at the xiphoid process over 5 days. We used, as predictors, combinations of temperature thresholds (29°C –31°C) and times, postinjection (18–36 h). A receiver-operator curve, sensitivity, and specificity were determined. A Distress Index value was calculated for the threshold conditions. The optimum detection threshold (highest Youden index) was found at Ts ⩽ 30.5°C at 24 h (90% specific, 84% sensitive). This threshold condition reduced animal suffering by 41% while providing an accurate survival rate estimate. Using this threshold, only 13 of 154 mice would have died from sepsis; 67 would have been euthanized at 24 h, and only 7 of 154 would have been euthanized unnecessarily. In conclusion, using a humane endpoint of Ts ⩽ 30.5°C at 24 h accurately predicts mortality and can effectively reduce animal suffering during CS survival protocols.